Hubungan Lama Penggunaan Kontrasepsi KB Suntik 3 Bulan dengan Peningkatan Berat Badan Akseptor KB di Posyandu Melati Bajeng Kabupaten Gowa - Nurhaqni Anggraeni; Muhamad Isnaini; Asriani Bahar (Prodi Keperawatan Universitas Syekh Yusuf Al Makassari Gowa, 2025)
Family planning is an effort to achieve prosperity by providing marriage advice, infertility treatment and birth spacing. Family planning is an act of helping individuals or married couples to avoid unwanted births, get births that they really want, and regulate the interval between births. Family planning is a conscious process by couples to decide the number and spacing of children and the time of birth. According to WHO, the number of injectable contraceptive users worldwide is 4,000,000 or around 45%. In the United States, the number of injectable contraceptives used is 30%, while in Indonesia injectable contraceptives are one of the most popular contraceptives. Contraception in Indonesia is most popular, namely injectable contraception at 34.3%. The type of research used is quantitative. The design of this research aims to determine the relationship between the duration of injectable contraceptive use for 3 months and the increase in body weight in contraceptive acceptors. The instruments used by researchers were questionnaires and interviews. Of the 27 respondents who used 3-month injectable contraceptives for >1 year, 17 were acceptors (63.0), and 10 were acceptors for ≤1 year (37.0), while 17 of the 27 respondents experienced weight gain (63.0) and those who did not experienced increase in body weight of 10 acceptors (37.0), chi-square test results ρ value: 0.285 (>0.05) this identifies Ho as there is no relationship between the duration of using injectable contraceptives for 3 months with an increase in body weight.